Corneal tomographic changes during corneal rigid gas-permeable contact lens wear in keratoconic eyes. Issue 2 (10th November 2020) - Koh, Shizuka; Inoue, Ryota; Maeda, Naoyuki; Oie, Yoshinori; Jhanji, Vishal; Miki, Atsuya; Nishida, Kohji
Abstract : Background/Aims: We aimed to investigate the refractive changes in the posterior corneal surface in keratoconus (KC) associated with wearing spherical corneal rigid gas-permeable contact lenses (corneal GPs) with apical touch or three-point touch fitting and the effect of spherical corneal GPs on corneal biomechanics. Methods: Patients with KC wearing corneal GPs every day without facing complications were enrolled as a single group. Corneal tomographic data were obtained using a three-dimensional anterior segment optical coherence tomography from the same eye with and without corneal GPs. Dioptric data from the central 3-mm zone of the posterior corneal surface were decomposed into spherical, regular astigmatism, asymmetry and higher-order irregularity components using Fourier harmonic analysis. The corneal biomechanical indices were deformation amplitude ratio within 2 mm, integrated radius, stiffness parameter at first applanation and linear Corvis Biomechanical Index. Correlations between the difference in Fourier indices with and without corneal GPs and the corneal biomechanical parameters were analysed. Results: Thirty-two eyes of 32 patients with KC were enrolled. Spherical, regular astigmatism and asymmetry components were significantly smaller with corneal GP wear than without the wear (all p<0.001). All biomechanical indices were significantly correlated with the difference in the spherical components with and without corneal GPs. Conclusion: Corneal biomechanical properties of KC were correlated with posterior corneal surface flattening induced by wearing corneal GPs on the spherical components. This effect is greater in biomechanically weaker corneas.